A gender perspective on appearance-related concerns and its manifestations among persons born with unilateral cleft lip and palate. Issue 6 (3rd July 2021) - Paganini, Anna; Moss, Tim; Persson, Martin; Mark, Hans
ABSTRACT: Cleft lip and palate (CLP) affects a person's facial appearance and can cause appearance-related distress. Appearance-related distress and its manifestations are not fully understood. Women with CLP tend to experience a higher degree of distress as well as undergo more aesthetic revisions than men. The aim of this study was to investigate if self-reported appearance-related gender differences occur among adults born with unilateral CLP using the Derriford Appearance Scale 24 (DAS24). One hundred sixty two consecutive patients, 107 men and 55 women, with unilateral CLP and no associated syndromes treated at the same hospital were asked to answer the DAS24. A mixed methods approach was used to analyse the questionnaires both quantitively and qualitatively. Fifty men and 30 women participated, the results showed that the aspects of appearance considered most disturbing was cleft-related among both genders, most common in regards to the nose. Three themes were found: acceptance, cleft features, and general appearance issues. The quantitative part showed that women reported higher appearance-related social anxiety and avoidance than men. This study demonstrated that appearance-related distress is present in both genders; however, women expressed more distress than men. Moreover, non-cleft as well as cleft features are of importance for self-reported dissatisfaction.